2010
DOI: 10.1017/s1041610210000165
|View full text |Cite
|
Sign up to set email alerts
|

Changes to psychotropic medications in the six months after admission to nursing homes in Melbourne, Australia

Abstract: Judging from epidemiological data, treatment revisions were almost certainly insufficient to address residents' mental health needs. We discuss ways of harnessing existing nursing and pharmacy resources to ensure better care for aged residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 34 publications
(45 reference statements)
4
34
1
Order By: Relevance
“…One study found that people received psychotropic drugs over at least one year despite uncertainty about symptom improvement and another study showed that most antipsychotic prescriptions remained unchanged over a six-month period [17,18]. In the present study, 63/111 (57%) received exactly the same antipsychotic dose after six months.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…One study found that people received psychotropic drugs over at least one year despite uncertainty about symptom improvement and another study showed that most antipsychotic prescriptions remained unchanged over a six-month period [17,18]. In the present study, 63/111 (57%) received exactly the same antipsychotic dose after six months.…”
Section: Discussionmentioning
confidence: 44%
“…Selbæk et al also demonstrated that most symptoms show an intermittent course which does not support long-term treatment with antipsychotics [18]. O’Connor et al discuss the fact that the person’s symptoms are classified as present when in reality they occur only occasionally [17]. These findings stress the importance of reviewing antipsychotic use regularly to ensure that the indication remains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In reality, despite regular warnings and recommendations to the contrary, the high use of psychotropic medications remains resistant to change. An increase in the need for medication on entry to care might be expected given the increased disorientation and confusion of some older adults during this transition, but this should stabilize in time.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…There is a high prevalence of depression in aged care residents with dementia (e.g., McCabe et al ., ), and recent Australian surveys point to an inadequate approach to the management of depression in this setting (McSweeney and O'Connor, ; O'Connor et al ., ). McSweeney and O'Connor () found that, whereas 83% of residents with major depression and dementia eventually received antidepressant medication during their study, up to 42% continued to satisfy diagnostic criteria for major depression at 6‐month follow‐up, despite treatment.…”
Section: Introductionmentioning
confidence: 99%